Praktikalitas Media Pembelajaran Interaktif pada Proses Pembelajaran Rangkaian Listrik - Doni Tri Putra Yanto (Universitas Negeri Padang, 2019)
This study discuss about the practicality of interactive instructional media on Electrical Circuits Learning Process with students grade X in Technical and Vocational Middle School (SMK) 5 Padang. This research will reveal the practicality level of the use of interactive instructional media both by teachers and students after using this interactive learning media in the learning process. Subjects in this study were 2 teachers and 30 students. Questionnaire sheets that have been validated by experts were used as instruments in this study to collect teacher response data and student responses related to media practicality. The data obtained is processed using descriptive analysis techniques by referring to the systematic steps of practicality testing. The results showed that based on the teacher's response, the practicality level of the media was very practical, whereas based on the students' responses, the practicality level of learning media was also very practical. So, it can be concluded that interactive instructional media is very practical to be used by teachers and students in the Electrical Circuit learning process.